Model predictive control of continuous layering granulation in fluidised beds with internal product classification. (September 2016) - Bück, Andreas; Dürr, Robert; Schmidt, Martin; Tsotsas, Evangelos
Abstract : Highlights: Feedback control design for continuous fluidised bed layering with internal product classification. Constrained model predictive control for stabilisation of steady-states. Investigation of controller performance under model-mismatch. Abstract: Continuous fluidised bed layering with internal product separation is known to possess unstable steady-states, yielding sustained nonlinear oscillations in the particle size distribution, the key product parameter. In this work, the well-known framework of constrained linear model predictive control is applied to stabilise corresponding unstable steady-states. Performance of the controllers is discussed with respect to design parameters and process constraints, as is robustness to overspray generation and size of formed overspray particles.